Expertise and decision-making in American football - Woods, Adam J.; Kranjec, Alexander; Lehet, Matt; Chatterjee, Anjan (Frontiers in Psychology, 2015)
In American football, pass interference calls can be difficult to make, especially when the timing of contact between players is ambiguous. American football history contains many examples of controversial pass interference decisions, often with fans, players, and officials interpreting the same event differently. The current study sought to evaluate the influence of experience with concepts important for officiating decisions in American football on the probability (i.e., response criteria) of pass interference calls. We further investigated the extent to which such experience modulates perceptual biases that might influence the interpretation of such events. We hypothesized that observers with less experience with the American football concepts important for pass interference would make progressively more pass interference calls than more experienced observers, even when given an explicit description of the necessary criteria for a pass interference call. In a go/no-go experiment using photographs from American football games, three groups of participants with different levels of experience with American football (Football Naïve, Football Player, & Football Official) made pass interference calls for pictures depicting left-moving and right-moving events. More experience was associated with progressively and significantly fewer pass interference calls (F (2, 48) = 10.4, p < .001), with Football Naïve participants making the most pass interference calls, and Football Officials the least. In addition, our data replicated a prior finding of spatial biases for interpreting left-moving images more harshly than identical right-moving images, but only in Football Players. These data suggest that experience with the concepts important for making a decision may influence the rate of decision-making, and may also play a role in susceptibility to spatial biases.